2017
DOI: 10.1002/cmdc.201700082
|View full text |Cite
|
Sign up to set email alerts
|

Improving Nonspecific Binding and Solubility: Bicycloalkyl Groups and Cubanes as para‐Phenyl Bioisosteres

Abstract: Bicycloalkyl groups have been previously described as phenyl group bioisosteres. This article describes the synthesis of new building blocks allowing their introduction into complex molecules, and explores their use as a means to modify the physicochemical properties of drug candidates and improve the quality of imaging agents. In particular, the replacement of an aromatic ring with a bicyclo[1.1.1]pentane-1,3-diyl (BCP) group improves aqueous solubility by at least 50-fold, and markedly decreases nonspecific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
109
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(113 citation statements)
references
References 34 publications
1
109
0
3
Order By: Relevance
“…If the para ‐substituted arene of the drug molecule influences the conformation of the molecule or has a role in the pharmacophore (e.g., π–π staking)—an aliphatic bioisostere will not be effective. It was shown that BCP improves aqueous solubility by at least 50‐fold and markedly decreases nonspecific binding (NSB) . On the other hand, BCO increased the lipophilicity of the molecules but did not show the same benefits regarding NSB or solubility.…”
Section: Application Of Rigid‐linear Linkers In Small Molecule Drugsmentioning
confidence: 99%
See 3 more Smart Citations
“…If the para ‐substituted arene of the drug molecule influences the conformation of the molecule or has a role in the pharmacophore (e.g., π–π staking)—an aliphatic bioisostere will not be effective. It was shown that BCP improves aqueous solubility by at least 50‐fold and markedly decreases nonspecific binding (NSB) . On the other hand, BCO increased the lipophilicity of the molecules but did not show the same benefits regarding NSB or solubility.…”
Section: Application Of Rigid‐linear Linkers In Small Molecule Drugsmentioning
confidence: 99%
“…A number of different tyrosine 325 h and phenylalanine 325 g derivatives have also been reported in the literature . BCP analogues of these natural amino acids were made to elucidate conformational and electronic effects in peptides.…”
Section: Application Of Rigid‐linear Linkers In Small Molecule Drugsmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, in the key-step of this protocol, the olefin in 20 was subjected to Carriera hydrohydrazination conditions to generate the diazo compound 21. 22 Deprotection of the Boc functionality with trifluoroacetic acid gave the hydrazine intermediate, which in turn could be converted to the amine 22 with the help of samarium diiodide. Finally, acid hydrolysis of 22 yielded the hydrolyzed product 23 to complete our racemic synthesis of thetyrosine-BCP ethyl ester.…”
Section: Scheme 1 Retrosynthetic Analysis Ofmentioning
confidence: 99%